Nilakantha- Syed Double Series

Calculus Level 5

m = 0 k = 0 ( 1 ) m + 1 ( 2 m + 3 ) 2 k + 3 ( ( 2 m + 3 ) 2 1 ) = π a b π c d e f \sum _{ m=0 }^{ \infty }{ \sum _{ k=0 }^{ \infty }{ \frac { { \left( -1 \right) }^{ m+1 } }{ { \left( 2m+3 \right) }^{ 2k+3 }\left( { \left( 2m+3 \right) }^{ 2 }-1 \right) } } } =\frac { { \pi }^{ a } }{ b } -\frac { { \pi }^{ c } }{ d } -\frac { e }{ f }

The equation above holds true for positive integers a a , b b , c c , d d , e e , and f f with e e and f f being coprime integers. Find the value of a + b + c + d + e + f a+b+c+d+e+f .


The answer is 130.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Syed Shahabudeen
Feb 16, 2020

The series can be simplified and can be written as m = 1 k = 1 ( 1 ) m ( 2 m + 1 ) 2 k + 1 ( ( 2 m + 1 ) 2 1 ) = 1 4 m = 1 k = 1 ( 1 ) m ( 2 m + 1 ) 2 k + 1 ( m + 1 ) ( m ) \sum _{ m=1 }^{ \infty }{ \sum _{ k=1 }^{ \infty }{ \frac { { \left( -1 \right) }^{ m } }{ { \left( 2m+1 \right) }^{ 2k+1 }\left( { \left( 2m+1 \right) }^{ 2 }-1 \right) } } } =\frac { 1 }{ 4 } \sum _{ m=1 }^{ \infty }{ \sum _{ k=1 }^{ \infty }{ \frac { { \left( -1 \right) }^{ m } }{ { \left( 2m+1 \right) }^{ 2k+1 }\left( m+1 \right) \left( m \right) } } } which can be further simplified as 1 4 m = 1 ( 1 ) m ( 2 m + 1 ) ( m + 1 ) ( m ) k = 1 1 ( 2 m + 1 ) 2 k \frac { 1 }{ 4 } \sum _{ m=1 }^{ \infty }{ \frac { { \left( -1 \right) }^{ m } }{ \left( 2m+1 \right) \left( m+1 \right) \left( m \right) } \sum _{ k=1 }^{ \infty }{ \frac { 1 }{ { \left( 2m+1 \right) }^{ 2k } } } } since second series is a geometric series so we get k = 1 1 ( 2 m + 1 ) 2 k = 1 ( 2 m + 1 ) 2 1 = 1 4 ( m + 1 ) ( m ) \sum _{ k=1 }^{ \infty }{ \frac { 1 }{ { \left( 2m+1 \right) }^{ 2k } } } =\frac { 1 }{ { \left( 2m+1 \right) }^{ 2 }-1 } =\frac { 1 }{ 4\left( m+1 \right) \left( m \right) } on substitution we get 1 16 m = 1 ( 1 ) m ( 2 m + 1 ) ( m + 1 ) 2 ( m ) 2 \frac { 1 }{ 16 } { \sum _{ m=1 }^{ \infty }{ \frac { { \left( -1 \right) }^{ m } }{ \left( 2m+1 \right) { \left( m+1 \right) }^{ 2 }{ \left( m \right) }^{ 2 } } } } by partial fraction decomposition and by evaluating each series we get 1 16 m = 1 ( 4 ( 1 ) m + 1 m + ( 1 ) m m 2 + 4 ( 1 ) m + 1 m + 1 + ( 1 ) m + 1 ( m + 1 ) 2 + 16 ( 1 ) m ( 2 m + 1 ) ) = 1 16 ( ( 4 ln 2 ) π 2 12 + 4 4 ln 2 + 1 π 2 12 + 4 π 16 ) = π 4 π 2 96 11 16 \frac { 1 }{ 16 } { \sum _{ m=1 }^{ \infty }{ \left( \frac { { 4\left( -1 \right) }^{ m+1 } }{ m } +\frac { { \left( -1 \right) }^{ m } }{ { m }^{ 2 } } +\frac { 4{ \left( -1 \right) }^{ m+1 } }{ m+1 } +\frac { { \left( -1 \right) }^{ m+1 } }{ { \left( m+1 \right) }^{ 2 } } +\frac { { 16\left( -1 \right) }^{ m } }{ \left( 2m+1 \right) } \right) } }=\frac { 1 }{ 16 } \left( (4\ln { 2)-\frac { { \pi }^{ 2 } }{ 12 } +4-4\ln { 2+1-\frac { { \pi }^{ 2 } }{ 12 } +4\pi -16 } } \right) =\frac { \pi }{ 4 } -\frac { { \pi }^{ 2 } }{ 96 } -\frac { 11 }{ 16 } therefore a + b + c + d + e + f = 1 + 4 + 2 + 96 + 11 + 16 = 130 \boxed{a+b+c+d+e+f=1+4+2+ 96+11+16 = 130}

Chew-Seong Cheong
Feb 16, 2020

S = m = 0 k = 0 ( 1 ) m + 1 ( 2 m + 3 ) 2 k + 3 ( ( 2 m + 3 ) 2 1 ) = m = 0 ( 1 ) m + 1 ( 2 m + 3 ) 3 ( ( 2 m + 3 ) 2 1 ) k = 0 ( 1 ( 2 m + 3 ) 2 ) k = m = 0 ( 1 ) m + 1 ( 2 m + 3 ) 3 ( ( 2 m + 3 ) 2 1 ) × ( 2 m + 3 ) 2 ( 2 m + 3 ) 2 1 = m = 0 ( 1 ) m + 1 ( 2 m + 3 ) ( 4 m 2 + 12 m + 8 ) 2 = m = 0 ( 1 ) m + 1 ( 2 m + 3 ) ( 2 m + 2 ) 2 ( 2 m + 4 ) 2 By partial fraction decomposition = m = 0 ( 1 ) m + 1 4 ( 1 ( 2 m + 2 ) 2 2 2 m + 2 + 4 2 m + 3 1 ( 2 m + 4 ) 2 2 2 m + 4 ) = m = 0 ( 1 ) m 2 ( 1 2 m + 2 2 2 m + 3 + 1 2 m + 4 ) m = 0 ( 1 ) m 16 ( 1 ( m + 1 ) 2 1 ( m + 2 ) 2 ) = 1 2 ( 1 2 2 3 + 1 4 1 4 + 2 5 1 6 + 1 6 2 7 + ) 1 16 ( 1 1 2 1 2 2 1 2 2 + 1 3 2 + 1 3 2 1 4 2 ) = 1 4 1 + n = 0 ( 1 ) n 2 n + 1 + 1 16 1 8 n = 1 ( 1 ) n + 1 n 2 Riemann zeta function ζ ( s ) = k = 1 1 k s = 11 16 + tan 1 1 1 8 ( ζ ( 2 ) 1 2 ζ ( 2 ) ) and ζ ( 2 ) = π 2 6 = π 4 π 2 96 11 16 \begin{aligned} S & = \sum_{m=0}^\infty \sum_{k=0}^\infty \frac {(-1)^{m+1}}{(2m+3)^{2k+3}\left((2m+3)^2-1\right)} \\ & = \sum_{m=0}^\infty \frac {(-1)^{m+1}}{(2m+3)^3\left((2m+3)^2-1\right)} \sum_{k=0}^\infty \left(\frac 1{(2m+3)^2}\right)^k \\ & = \sum_{m=0}^\infty \frac {(-1)^{m+1}}{(2m+3)^3\left((2m+3)^2-1\right)} \times \frac {(2m+3)^2}{(2m+3)^2 - 1} \\ & = \sum_{m=0}^\infty \frac {(-1)^{m+1}}{(2m+3)\left(4m^2+12m+8\right)^2} \\ & = \sum_{m=0}^\infty \frac {(-1)^{m+1}}{(2m+3)(2m+2)^2(2m+4)^2} & \small \blue{\text{By partial fraction decomposition}} \\ & = \sum_{m=0}^\infty \frac {(-1)^{m+1}}4 \left(\frac 1{(2m+2)^2} - \frac 2{2m+2} + \frac 4{2m+3} - \frac 1{(2m+4)^2} - \frac 2{2m+4} \right) \\ & = \sum_{m=0}^\infty \frac {(-1)^m}2 \left(\frac 1{2m+2} - \frac 2{2m+3} + \frac 1{2m+4} \right) - \sum_{m=0}^\infty \frac {(-1)^m}{16} \left(\frac 1{(m+1)^2} - \frac 1{(m+2)^2} \right) \\ & = \small \frac 12 \left(\frac 12 - \frac 23 + \frac 14 - \frac 14 + \frac 25 - \frac 16 + \frac 16 - \frac 27 + \cdots \right) - \frac 1{16} \left(\frac 1{1^2} - \frac 1{2^2} - \frac 1{2^2} + \frac 1{3^2} + \frac 1{3^2} - \frac 1{4^2} - \cdots \right) \\ & = \frac 14 - 1 + \sum_{n=0}^\infty \frac {(-1)^n}{2n+1} + \frac 1{16} - \frac 18 \sum_{n=1} \frac {(-1)^{n+1}}{n^2} & \small \blue{\text{Riemann zeta function }\zeta (s) = \sum_{k=1}^\infty \frac 1{k^s}} \\ & = - \frac {11}{16} + \tan^{-1} 1 - \frac 18 \left(\zeta (2) - \frac 12 \zeta(2)\right) & \small \blue{\text{and }\zeta (2) = \frac {\pi^2}6} \\ & = \frac \pi 4 - \frac {\pi^2}{96} - \frac {11}{16} \end{aligned}

Therefore a + b + c + d + e + f = 1 + 4 + 2 + 96 + 11 + 16 = 130 a+b+c+d+e+f = 1 + 4 + 2 + 96 + 11 + 16 = \boxed{130} .


Reference: Riemann zeta function

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...